2014
DOI: 10.1063/1.4897093
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation effect on the chemical composition and the antioxidant activity of Ipomoea batatas L.

Abstract: Abstract. The chemical composition and antioxidant activity of Ipomoea batatas L. (sweet potato) were studied by xray fluorescence (XRF) spectroscopy, Fourier transform infrared spectroscopy, and by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity. The irradiation treatment was performed by using Cs-137 as a gamma sources in experimental equipment. Treatment by irradiation emerges as a possible conservation technique that has been tested successfully in several food products. The amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…1. The strong and wide absorption peak of C-C is come from activated charcoal at 1563 cm -1 [5,[7][8][9][10]. Table 1 shows chemical oxide composition of activated charcoal, hydrogel polymer, and composites from XRF spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…1. The strong and wide absorption peak of C-C is come from activated charcoal at 1563 cm -1 [5,[7][8][9][10]. Table 1 shows chemical oxide composition of activated charcoal, hydrogel polymer, and composites from XRF spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study was reported in Ref. [5] for the effect of cooking process by gamma irradiation of Ipomoea batatas L to the composition, the structural properties, and the anti-oxidant activity.…”
Section: Introductionmentioning
confidence: 99%